Single nucleotide polymorphism rs854560 in paraoxonase-1 regulates the cytodifferentiation of human periodontal ligament cells - Masumoto, Risa; Fujihara, Chiharu; Matsumoto, Masahiro; Kitagaki, Jirouta; Murakami, Shinya (Frontiers in Dental Medicine, 2024)
Aggressive periodontitis (AgP), classified as Stages III or IV and grade C periodontitis, is characterized by the rapid destruction of periodontal tissue. Genetic factors contribute to the pathogenesis of this disease, and familial aggregation of periodontitis is often observed. However, the mechanisms underlying the onset or progression of AgP have not been elucidated. Previously, we performed exome sequencing and identified AgP risk factors in Japanese AgP-patients. However, the small sample size limited our scope for detecting some of the true AgP genetic risk factors. To overcome this limitation, we searched for AgP-related genes more comprehensively from the whole exome sequencing data of the Japanese AgPpatients by extending the filtering criteria range. We identified seven AgP-associated suggestive genes, including the single nucleotide polymorphism (SNP) rs854560 in paraoxonase-1 (PON-1), which is correlated with AgP. However, the mechanism(s) underlying the induction of AgP pathogenesis by the SNP rs854560 PON-1 has not been elucidated. Thus, we further analyzed the functions of the SNP rs854560 PON-1 in human periodontal ligament (HPDL) cells through transfection of the wild-type PON-1 (WT) or SNP rs854560 PON-1 (mut) into HPDL cells. Real-time PCR indicated that mut had higher mRNA expression of osteogenic related-genes and showed a higher tendency of ALP activity and proliferation. The result suggested that WT PON-1 contributes to periodontal tissue homeostasis through appropriate proliferation and cytodifferentiation of HPDL cells, while SNP rs854560 PON-1 may mediate excessive calcification of periodontal tissue due to hyper proliferation of HPDL cells, thereby increasing the risk of AgP.